2021
DOI: 10.1038/s41598-021-86392-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic 31P-MRI and 31P-MRS of lower leg muscles in heart failure patients

Abstract: Impaired oxidative metabolism is one of multi-variate factors leading to exercise intolerance in heart failure patients. The purpose of the study was to demonstrate the use of dynamic 31P magnetic resonance spectroscopy (MRS) and 31P magnetic resonance imaging (MRI) techniques to measure PCr resynthesis rate post-exercise as a biomarker for oxidative metabolism in skeletal muscle in HF patients and controls. In this prospective imaging study, we recruited six HF patients and five healthy controls. The imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 40 publications
0
21
1
Order By: Relevance
“…HF is associated with impaired oxidative skeletal muscle metabolism as shown by dynamic in vivo measurements with 31 phosphorus (31P) magnetic resonance spectroscopy (MRS) [ 2 , 68 , 69 , 118 ]. This technique, which allows for quantification of high-energy phosphate decline rates during exercise and post-exercise rates of recovery, provides an adequate method for assessing in vivo mitochondrial oxidative metabolism.…”
Section: Pathophysiology Of Exercise Intolerance In Heart Failurementioning
confidence: 99%
See 4 more Smart Citations
“…HF is associated with impaired oxidative skeletal muscle metabolism as shown by dynamic in vivo measurements with 31 phosphorus (31P) magnetic resonance spectroscopy (MRS) [ 2 , 68 , 69 , 118 ]. This technique, which allows for quantification of high-energy phosphate decline rates during exercise and post-exercise rates of recovery, provides an adequate method for assessing in vivo mitochondrial oxidative metabolism.…”
Section: Pathophysiology Of Exercise Intolerance In Heart Failurementioning
confidence: 99%
“…This technique, which allows for quantification of high-energy phosphate decline rates during exercise and post-exercise rates of recovery, provides an adequate method for assessing in vivo mitochondrial oxidative metabolism. Previous studies showed an increased depletion of highly energetic phosphates and a prolonged phosphocreatine (PCr) recovery rate, implying that oxidative mitochondrial function in skeletal muscle is impaired in HF during exercise [ 2 , 69 , 119 , 120 ]. A detected decrease in intramuscular pH during exercise [ 68 , 69 ] and increase in blood lactate levels [ 100 ] in HF compared with healthy subjects furthermore suggest that abnormal skeletal muscle metabolism induces an earlier shift from oxidative metabolism to glycolytic metabolism, as discussed below.…”
Section: Pathophysiology Of Exercise Intolerance In Heart Failurementioning
confidence: 99%
See 3 more Smart Citations